1999
DOI: 10.1046/j.1365-2672.1999.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival ability of cytotoxic strains of motile Aeromonas spp. in different types of water

Abstract: The ability of motile Aeromonas spp. to survive in drinking water (mineral and tap water) and in sea water was experimentally tested. Clinically isolated cytotoxic strains of A. hydrophila, A. caviae and A. sobria were selected for this study. After contamination of water samples, the survival of Aeromonas strains was studied for at least three months using viable counts. The results obtained show that the survival of the Aeromonas spp. varies considerably depending on species and water type. For all three spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…The initial rapid growth seen with the A. hydrophila aroA strain after inoculation of nonsterilized water microcosms has also been reported for other A. hydrophila strains (10,18) as well as for other species, such as Vibrio vulnificus (11), Pseudomonas aeruginosa (35,69), and Photobacterium damselae subsp. damselae (21), and appears to be correlated with the water volume and the recipient surface (34).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The initial rapid growth seen with the A. hydrophila aroA strain after inoculation of nonsterilized water microcosms has also been reported for other A. hydrophila strains (10,18) as well as for other species, such as Vibrio vulnificus (11), Pseudomonas aeruginosa (35,69), and Photobacterium damselae subsp. damselae (21), and appears to be correlated with the water volume and the recipient surface (34).…”
Section: Discussionsupporting
confidence: 59%
“…Several studies concerning the survival of A. hydrophila strains in aquatic environments, such as distilled water (44), mineral water (18,45,47), tap water (43), and seawater (40), have been published. Microcosms are often used in these studies, most of them applied to assess the health impact of the presence of motile Aeromonas species in drinking water, because the production of a wide range of virulence factors is a common feature of virulent strains (10,13,53,54,64).…”
Section: Cfu MLmentioning
confidence: 99%
“…VBNC forms appeared during the first days of the microcosm incubation ( figure 1a). Similar results were reported by LAABErKi (1999), LAKhAL (2003) and MAALEj et al (2004) for the survival of A. hydrophila in marine water, and for BrANDi et al (1999), MAry et al (2002) and MESSi et al (2002) for survival ability of A. hydrophila in different water types. The results obtained for A. hydrophila survival in marine water after incubation in waste water showed a greater progressive decline in the plate count number (2.74 log units) (figure 1b).…”
Section: Resultssupporting
confidence: 82%
“…Survival of Aeromonas in water microcosms is the subject of much debate as high-survival rates (Warburton et al 1994;Tsai and Yu 1997;Brandi et al 1999) and lowsurvival rates (Lowcock and Edwards 1994;Kersters et al 1996) have been reported. However, it is likely that interpretation of water viability studies depends, to a large extent, upon the specific conditions during and even before the actual experiments, including the bacterial strains used and their growth history (Rozen and Belkin 2001).…”
Section: Discussionmentioning
confidence: 99%